A new species and three newly recorded species of the dacnusine genus Dacnusa Haliday (Hymenoptera: Braconidae: Alysiinae) from China - Zheng, Min-Lin; Chen, Jia-Hua (Zootaxa, 2017)
A new species of the genus Dacnusa from the Palaearctic region of China, Dacnusa (Pachysema) heterodentatus sp. nov. is described. As well, three newly recorded species from the Palaearctic region in China are reported, along with their descriptions and illustrations: Dacnusa (Agonia) adducta (Haliday), Dacnusa (Aphanta) sasakawai Takada and Dacnusa (Dacnusa) maculipes Thomson. A key is presented to the subgenera of Dacnusa and the most similar species to these four reported species.